Detection of Extended Spectrum B-Lactamases in Urinary Isolates of Klebsiella pneumoniae in Relation to Bla(SHV), Bla(TEM) and Bla(CTX-M) Gene Carriage - Eftekhar, F (Tehran University of Medical Sciences, 2012)
BACKGROUND: Resistance to contemporary broad-spectrum β-lactam antibiotics mediated by extended-spectrum β-lactamases (ESBLs) is increasing worldwide. Klebsiella pneumoniae, an important cause of nosocomial and community acquired urinary tract infections has rapidly become the most common ESBL producing organism. We examined ESBL production in urinary isolates of K. pneumoniae in relation to the presence of bla(SHV), bla(TEM) and bla(CTX-M) genes. METHODS: Antibiotic resistance of 51 clinical isolates of K. pneumoniae was determined to amoxicillin, amikacin, ceftazidime, cefotaxime, cefteriaxon, ceftizoxime, gentamicin, ciprofloxacin and nitrofurantoin by disc diffusion. Minimum inhibitory concentrations were also measured for ceftazidime, cefotaxime, cefteriaxon, ceftizoxime and ciprofloxacin. ESBL production was detected by the double disc synergy test and finally, presence of the bla(SHV), bla(TEM) and bla(CTX-M) genes were shown using specific primers and PCR. RESULTS: Disc diffusion results showed that 96.08 % of the isolates were resistant to amoxicillin followed by 78.43 % resistance to nitrofurantoin, 49.02 % to amikacin and ceftazidime, 41.17 % to ceftriaxone, 37.25% resistance to cefotaxime and ceftizoxime, and 29.42 % to gentamicin and ciprofloxacin. Both resistant and intermediately resistant organisms were resistant in MIC determinations. Twenty two isolates (43.14%) carried bla(SHV), 18 (35.29%) had bla(TEM) and 16 (31.37%) harbored bla(CTX-M) genes. ESBL production was present in 14 isolates (27.45 %) of which, 3 did not harbor any of the 3 genes. Among the non-ESBL producers, 9 lacked all 3 genes and 2 carried them all. CONCLUSION: No relation was found between gene presence and ESBL expression.